Do functional changes occur in the bladder due to bladder outlet obstruction? ‐ ICI‐RS 2018. (6th July 2019) - Bosch, Ruud; Abrams, Paul; Averbeck, Marcio Augusto; Finazzi Agró, Enrico; Gammie, Andrew; Marcelissen, Tom; Solomon, Eskinder
Abstract: Studies on bladder dysfunction (BD), more specifically functional‐urodynamic changes in the bladder as a result of bladder outlet obstruction (BOO) have been summarized for this TT. Based on available, but limited evidence from human studies a three‐stage model can be hypothesized to characterize BOO‐induced bladder remodeling: hypertrophy, compensation (increased detrusor contractility during the voiding phase, often in combination with filling phase detrusor overactivity) followed by the phase of decompensation [detrusor underactivity]. The time between the start of compensation and eventual decompensation seems to be determined by age of onset, severity, and type of obstruction and clinical mitigating factors such as vascular and metabolic problems. Understanding the relative contributions of these factors may allow the development of personalized timelines and probabilities for these obstructed patients.